Penerapan Virtual Tour 360 Derajat Sebagai Media Informasi Yayasan Al-Musaddadiyah Garut - Latifah, Ayu; Antika, Dini (Jurnal Algoritma, 2025)
The advancement of technology in the modern era has driven new innovations, including the use of Virtual Reality (VR) in various fields, one of which is education. Yayasan Al Musaddadiyah Garut, as an educational institution, requires an interactive information medium to introduce its facilities and buildings to the wider community and prospective students. This study aims to develop and evaluate the implementation of a 360° Virtual Tour based on Virtual Reality Photography (VRP) as an informational medium for Yayasan Al Musaddadiyah Garut. Using the Multimedia Development Life Cycle (MDLC) methodology, this research goes through six main stages: concept, design, material collection, assembly, testing, and distribution. The development process was carried out using the Insta360 X3 camera for 360° image capture and 3DVista software for virtual tour creation. The results show that this 360° Virtual Tour can provide comprehensive and interactive information about the foundation’s facilities. Testing was conducted using the black box testing method and a satisfaction survey involving 20 respondents from a population of over 2000 within the Foundation, resulting in an average satisfaction score of 4.57 out of 5. The main contribution of this research is the provision of an innovative VR-based information medium that can enhance the transparency and appeal of Yayasan Al Musaddadiyah Garut for prospective students and the general public. The research also provides recommendations for improving visual features and interactivity for further development.